Livstegn. En semiotisk analyse af CD4-celletal hos HIV-smittede - Seeberg, Jens (Tidsskriftet Antropologi, 2019)
CD4-cells play a vital part for the body’s capability to overcome diseases. As a result of HIV-infection these cells are destroyed. Counts of the cells inform both the doctor and the HIV-infected person of the progress of the HIV-infection which may otherwise be unnoticed during the so-called latency period. The article analyzes the different and partly contradictory interpretations of CD4-counts throughout the course of the HIV-infection as well as their different potential for objectivization and corresponding possibilities for taking action. The article points to the necessity for medical doctors to acknowledge the symbolic content of the clinical tests rather than dismiss their patients’ worries as unfounded in physiological and bodily changes.